Utilization of Nanotechnology in the Development of Organic Fertilizers and Pesticides - Maria Estevez (International Journal of Science and Society, 2020)
The development of technology and its utilization cannot be denied that it is closely related to increasing the competitiveness of a country's industry. Increased knowledge and mastery of new technology is needed to win the competition in the era of global trade both by the government and industry. One example of technology that is being discussed hot is nanotechnology. The use of nano technology is well known, including in the fields of health, cosmetics and agriculture. Basically, the principle of nanotechnology discovery is to maximize yield or crop production by minimizing the use of fertilizers, pesticides and other needs by monitoring soil conditions such as roots and applying them directly to the target so that nothing is wasted. For pesticides, if this is applied it will be able to minimize the use of pesticides on plants because only target insects are affected. The use of nano technology in fertilizers will allow the release of nutrients contained in the fertilizer can be controlled. So only nutrients that will actually be absorbed by plants are released, so that there is no loss of nutrients there are undesirable targets such as soil, water and microorganisms. In nano fertilizers, nutrients can be in the form of nanomaterial encapsulation, coating by a thin protective layer or released in the form of an emulsion from nanoparticles.